Fungsi Sosial Pada Komunitas Sepeda Motor di Surakarta - Nuski Yuwafi, Maulana (2016)
This study aims to find, understand, and describe the social function of the motorcycle community to its environment. This research is kualiatif and research informant was a member of the motorcycle community in Surakarta. Data from this study were obtained using an open questionnaire. The results showed that the social function of the motorcycle community in the scope of internal among others, as a forum to establish communication and closeness among motorcycle users with the same brand, members of the motorcycle can exchange information on the development of automotive and raise awareness in road traffic, in addition to it also as a medium for mutual aid among members in all areas of life. The social function of the motorcycle community to society, among others, held a blood donation, charity, tree planting, shoulder to shoulder to help victims of natural disasters. The motorcycle community to help the police in conducting outreach to the general public about the traffic rules of behavior that are expected to become an example of safe driving. Key word : social function, community motorcycle, Surakarta